Application of nano-patterned InGaN fabricated by self-assembled Ni nano-masks in green InGaN/GaN multiple quantum wells. (1st April 2023) - Peng, Ruoshi; Xu, Shengrui; Fan, Xiaomeng; Tao, Hongchang; Su, Huake; Gao, Yuan; Zhang, Jincheng; Hao, Yue
Abstract: The nano-patterned InGaN film was used in green InGaN/GaN multiple quantum wells (MQWs) structure, to relieve the unpleasantly existing mismatch between high indium content InGaN and GaN, as well as to enhance the light output. The different self-assembled nano-masks were formed on InGaN by annealing thin Ni layers of different thicknesses. Whereafter, the InGaN films were etched into nano-patterned films. Compared with the green MQWs structure grown on untreated InGaN film, which on nano-patterned InGaN had better luminous performance. Among them the MQWs performed best when 3 nm thick Ni film was used as mask, because that optimally balanced the effects of nano-patterned InGaN on the crystal quality and the light output.